Technical guidelines for the safe movement of Musa germplasm (3rd edition) - Murray, Sharman; Lassois, Ludvine; Massart, Sébastien; Clerck, Caroline de; Caruana, Marie-Line; Chabannes, Pierre-Yves; Kumar, P. Lava; Houwe, Ines van den; Roux, Nicolas Stephan M.; Thomas, J.E. (2015)
These guidelines describe technical procedures that minimize the risk of pest introductions due to the movement of germplasm for research, crop improvement, plant breeding, exploration or conservation. It is important to emphasize that these guidelines are not meant for trade and commercial consignments concerning export and import of germplasm.